PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA KONTRAK DI KOTA SAMARINDA - Abraham Abraham (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
AbstractSometimes the presence of the union or unions at the company did not have the strength. The position of workers or contract workers is even more difficult, because the protection of the law for workers or contract workers is still weak.Population growth is higher and less balanced distribution of the population, a factor that greatly affects on employment issues in the homeland of Indonesia. In the literature of existing labor law, labor relations history in Indonesia begins with a very bleak future that slavery in which the oppression and inhuman treatment committed by parties capable of socio-economic as well as the rulers at that time.The contract workers can demand higher wages on employers as a result of the prices of basic necessities rise caused by rising fuel prices and employers reject wage hike demands of workers for reasons not yet expired letters of intent. The new labor agreement will expire in 2014.